SWITCHED RELUCTANCE MOTOR CONTROL BASED ON ADAPTIVE NEURO-FUZZY INFERENCE SYSTEM (ANFIS) - Nguyen Van Thanh (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2020)
This paper gives some studies on the model of Switched Resistor Motor (SRM). The adaptive neuro-fuzzy inference system (ANFIS) is used to model the inductance and moment of the SRM. Then, the PI Controller is applied to model the inductance and flux bond of the SRM. Comparing these two types of modeling method, it is clear that although the PI Controller method can do online research, it is not as accurate as ANFIS.